Single-Cell RNA Sequencing Reveals Macrophage Dynamics During MASH in Leptin-Deficient Rats - Xiaoming Xin; Yaohua Ni; Jing Wang; Fenglin Wu; Meichen Liu; Lingjuan Wu; Jiaxing Dai; Chenglin Wu; Xiaolei Song; Wang Zhang; Guangrui Yang; Ruling Shen; et al. (Cells)
Macrophages play important roles in metabolic dysfunction-associated steatohepatitis (MASH), an advanced and inflammatory stage of metabolic dysfunction-associated steatotic liver disease (MASLD). In humans and mice, the cellular heterogeneity and diverse function of hepatic macrophages in MASH have been investigated by single cell RNA sequencing (scRNA-seq). However, little is known about their roles in rats. Here, we collected liver tissues at the postnatal week 16, when our previously characterized Lep∆I14/∆I14 rats developed MASH phenotypes. By scRNA-seq, we found an increase in the number of macrophages and endothelial cells and a decrease in that of NK and B cells. Hepatic macrophages in rats underwent a unique M1 to M2 transition without expression of the classical markers such as Arg1 and Nos2, except for Cd163. Lipid-associated macrophages (LAMs) were increased, which could be detected by the antibody against Cd63. In the microenvironment, macrophages had an increased number of interactions with hepatocytes, myofibroblasts, T cells, neutrophils, and dendritic cells, while their interaction strengths remained unchanged. Finally, the macrophage migration inhibitory factor (MIF) pathway was identified as the top upregulated cell-communication pathway in MASH. In conclusion, we dissected hepatic macrophage dynamics during MASH at single cell resolution and provided fundamental tools for the investigation of MASH in rat models.